The Tortoisean Archetype: A Theory of Satire in Nigerian Drama - Adeoti, Gbemisola Remi (2014)
This paper attempt to stimulate literary discourse in the direction of a theoretical investigation of satiric drama by Nigerian playwrights and make certain suggestions, which will serve as starting step: towards a theory of satire in Nigerian drama. This will be done, taking due cognizance of the wide variety of Nigerians' indigenous cultural artistic experience.